The Effect of Implementation of the Learning Policies to Learning Management in Realizing Student’s Learning Outcomes (Reseach at Ma Nurul Huda Cibojong Cisurupan Garut) - Iska Fatmawati; Abdusy Syakur Amin; Ijudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Education is crucial to the growth of the individual as well as the society. In light of this, the government is fully committed to giving the education sector its full attention in the hopes that a well-functioning educational system will produce a future generation of citizens with moral character and the capacity to engage with society on a local, national, and international level. The low quality of education remains a significant issue in madrasah education. Suboptimal learning management is one of the causes of suboptimal curriculum implementation, leading to suboptimal student learning outcomes. This study aims to analyze the implementation of curriculum policy on learning management to achieve student learning outcomes. The research method used in this study is a descriptive analysis method with observation techniques, survey techniques, interview techniques, and documentation study techniques. The data analysis technique used to answer the hypotheses of the study is statistics with path analysis models. The population and respondents of this study are educators at Madrasah Aliyah Nurul Huda Cibojong Cisurupan Garut, totaling 47 respondents. The results of the main hypothesis testing using path analysis are